Unveiling the therapeutic symphony of probiotics, prebiotics, and postbiotics in gut-immune harmony - Zhou, Pengjun; Chen, Chunlan; Patil, Sandip; Dong, Shaowei (Frontiers in Nutrition, 2024)
The gut microbiota and immune system interaction play a crucial role in maintaining overall health.Probiotics, prebiotics, and postbiotics have emerged as promising therapeutic approaches to positively influence this complex axis and enhance health outcomes. Probiotics, as live bacteria, promote the growth of immune cells, shape immune responses, and maintain gut barrier integrity. They modify the gut microbiota by fostering beneficial bacteria while suppressing harmful ones. Additionally, probiotics interact with the immune system, increasing immune cell activity and anti-inflammatory cytokine production. Prebiotics, as indigestible fibres, selectively nourish beneficial microorganisms in the gut, enhancing gut microbial diversity and activity. This, in turn, improves gut health and boosts immune responses while controlling inflammation through its immunomodulatory properties.Postbiotics, produced during probiotic fermentation, such as short-chain fatty acids and antimicrobial peptides, positively impact gut health and modulate immune responses. Ensuring quality control and standardization will be essential for successful clinical implementation of these interventions. Overall, understanding and harnessing the gut microbiota-immune system interplay offer promising avenues for improving digestive and immunological health.